Análise do desempenho empresarial sob a ótica da sustentabilidade de uma empresa do setor calçadista - Nascimento, Nichelle Carolliny de Oliveira (2018)
The debate about the sustainability issue permeates several sectors of society and the business sector also stands on the issue. Therefore, companies are reflecting on the possibility of implementing strategies oriented towards sustainability, in order to justify the impacts of different productive activities and services on the environment and validate their social performance, precepts defended by the triple model. In this scenario, the footwear industry appears, as it generates more than 340,000 jobs and has a significant impact on the trade balance, but represents one of the main generators of hazardous industrial waste that can bring social risks worsening the quality of life of citizens. Given this panorama, efforts to mitigate its environmental and social impacts must be carried out. Therefore, this study had the objective of analyzing the business performance from the perspective of the sustainability of a footwear company, through a case study. In order to reach the objective, an adaptation of the GRID model of Corporate Sustainability was carried out through the consultation of specialists to insert specific indicators of the footwear industry. After the adaptation, the tool was applied as a test study. Once the necessary adjustments were made to the questionnaire, it was applied to a large company in João Pessoa, Paraíba. The results indicate that the company obtained a Corporate Sustainability Score 3 (Satisfactory), occupying position VIII, showing that it presents good economic performance, has good social interaction and is committed to environmental aspects. However, although it performed satisfactorily, the research shows that the company has indicators that should be improved, stimulating and guiding the adoption of a new and increasingly sustainable posture that can improve and influence the industry environment.